2021
DOI: 10.2196/preprints.31415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Impact of Social Media Information and Misinformation Producers on Health Information Seeking. Comment on “Health Information Seeking Behaviors on Social Media During the COVID-19 Pandemic Among American Social Networking Site Users: Survey Study” (Preprint)

Abstract: UNSTRUCTURED Our team's article serves as a response to Neely and colleagues' recent paper: Health Information Seeking Behaviors on Social Media During the COVID-19 Pandemic Among American Social Networking Site Users: Survey Study, wherein we provide additional information, challenge certain viewpoints, and provide future insight on the topic of how social media is influencing COVID-19 vaccination rates. While the original article suggests that social media serves as a determinant to C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…We understand and affirm the underlying spirit of Boudreau et al's [1] recommendation, and building on that, we would endorse an "all of the above" approach to the study of social media moving forward. A comprehensive research agenda-drawing on a diverse range of perspectives and methodological techniques-will be needed in order to understand and keep pace with social media's growing and evolving role in health information seeking.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…We understand and affirm the underlying spirit of Boudreau et al's [1] recommendation, and building on that, we would endorse an "all of the above" approach to the study of social media moving forward. A comprehensive research agenda-drawing on a diverse range of perspectives and methodological techniques-will be needed in order to understand and keep pace with social media's growing and evolving role in health information seeking.…”
supporting
confidence: 53%
“…As they point out, we surveyed a representative sample of American adults (N=1003) and found that most SNS users had not fact-checked COVID-19-related information with a medical professional, and those who had opted to follow credible, scientific sources on social media were significantly more likely to undergo vaccination [2]. In reply, Boudreau and colleagues noted that our study-and others like it-has focused primarily on consumers rather than the producers and publishers of medical content on social media [1]. They propose that researchers should shift their focus "from the consumers to the producers of this information," and, in particular, they emphasize the possibility of developing tools to assess and classify health-related posts on social media in order to help consumers distinguish medically valid guidance from potential misinformation.…”
mentioning
confidence: 78%
See 1 more Smart Citation